2010
DOI: 10.1124/jpet.110.172353
|View full text |Cite
|
Sign up to set email alerts
|

A Series of d-Amino Acid Oxidase Inhibitors Specifically Prevents and Reverses Formalin-Induced Tonic Pain in Rats

Abstract: We have found that mutation of D-amino acid oxidase (DAO) diminished formalin-induced tonic pain. The present research further studied the analgesic effects of a series of DAO inhibitors in this model. 5-Chlorobenzo[d]isoxazol-3-ol (CBIO), 4H-thieno[3,2-b]pyrrole-5-carboxylic acid (compound 8), 5-methylpyrazole-3-carboxylic acid (AS057278), sodium benzoate, and 4-nitro-3-pyrazole carboxylic acid (NPCA) inhibited rat spinal cord-derived DAO activity in a concentration-dependent manner, with maximal inhibition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 52 publications
3
53
0
Order By: Relevance
“…6-Chlorobenzo[d]isoxazol-3-ol (CBIO) is a potent competitive inhibitor of DAAO and has a K i value of 100 nM for porcine DAAO (Ferraris et al, 2008). Although its toxicity profile has not been fully established, CBIO has been tested in both mice and rats as treatment for pain and has resulted in no apparent toxicity (Gong et al, 2011;Lu et al, 2012). In another study, oral coadministration of CBIO with D-serine enhanced oral bioavailability of D-serine and its levels in the prefrontal cortex (Ferraris et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…6-Chlorobenzo[d]isoxazol-3-ol (CBIO) is a potent competitive inhibitor of DAAO and has a K i value of 100 nM for porcine DAAO (Ferraris et al, 2008). Although its toxicity profile has not been fully established, CBIO has been tested in both mice and rats as treatment for pain and has resulted in no apparent toxicity (Gong et al, 2011;Lu et al, 2012). In another study, oral coadministration of CBIO with D-serine enhanced oral bioavailability of D-serine and its levels in the prefrontal cortex (Ferraris et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…These observations, although counterintuitive to an understanding of the efficacy of NMDA receptor antagonists in models of pain, have also been described using sodium benzoate in neuropathic models (Zhao et al, 2010). In addition, others (Zhao et al, 2010;Gong et al, 2011Gong et al, , 2012Chen et al, 2012) reported on the effects of DAAO inhibition in a formalin model of tonic pain.…”
Section: Introductionmentioning
confidence: 92%
“…discovery program (Fang et al, 2007(Fang et al, , 2011Dorsey et al, 2008;Heffernan et al, 2009). In similar work, Gong et al (2011) described the close correlation between in vitro DAAO inhibitory potencies and intrathecal doses required for efficacy of structurally diverse DAAO inhibitors on formalin-induced tonic pain consistent with a downregulation of spinal DAAO blocked formalin-induced tonic pain (Chen et al, 2012). An alternative to the NMDA receptor mechanism, still consistent with DAAO inhibition, is the possibility that D-serine itself might be acting via a non-NMDA receptor target.…”
Section: Daao Inhibitor Neuropathic Painmentioning
confidence: 99%
See 1 more Smart Citation
“…Benzoic acid and its salts, including sodium benzoate, exist in many plants and are widely used as food preservatives [190]. Sodium benzoate also acts as a DAAO inhibitor and has favorable effects in NMDAR-based models such as pain relief [191,192] and glial cell death [193]. The potential molecular mechanisms of action of sodium benzoate remain to be determined.…”
Section: Indirect Augmentation Of Dsr Functionmentioning
confidence: 99%